2015
DOI: 10.1590/0074-02760140377
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hepatitis C viral clearance and hepatitis C chronic infection are associated with distinct cytokine profiles in Mexican patients

Abstract: The mechanisms related to the spontaneous clearance of hepatitis C virus (HCV) have been primarily studied in regions where the infection is endemic. Results of prior studies have been extrapolated to populations with low endemicity, such as Mexico. Herein, we determined the cytokine profiles in serum samples from Mexican patients who spontaneously cleared HCV and patients chronically infected with HCV genotype 1a. Chronic HCV-infected patients displayed increased interleukin (IL)-8 and regulated upon activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In this setting, we have explored the lipid profile of SC and CHC patients, but similar to miRNA results, both profiles were similar with no statistically significant differences among them. Similar results were found in a small study on CHC and SC Mexican patients [40], where both groups showed similarities in lipid profile but differences in liver enzymes and cytokines. However, a lipidomic analysis on the serum of HCV-resistant cases showed clear differences from HCV antibody-positive individuals, even those who clear viremia either spontaneously or after antiviral therapy [41].…”
Section: Discussionsupporting
confidence: 89%
“…In this setting, we have explored the lipid profile of SC and CHC patients, but similar to miRNA results, both profiles were similar with no statistically significant differences among them. Similar results were found in a small study on CHC and SC Mexican patients [40], where both groups showed similarities in lipid profile but differences in liver enzymes and cytokines. However, a lipidomic analysis on the serum of HCV-resistant cases showed clear differences from HCV antibody-positive individuals, even those who clear viremia either spontaneously or after antiviral therapy [41].…”
Section: Discussionsupporting
confidence: 89%
“…This could be the reason patients carrying the ∆G allele present greater liver damage. Furthermore, this hypothesis is consistent with recent findings that demonstrated that chronic HCV-infected patients express higher levels of interleukin-8 and RANTES in comparison with those who had SC [ 45 ]. Nonetheless, the impact of IL28B and IFNL4 polymorphisms on HCV-related disease progression is controversial [ 46 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Until this moment, evidences have suggested that the disrupted pattern of soluble inflammatory mediators induced by HCV infection remains even after viral clearance with DAA treatment, indicating that the inflammatory changes are not fully reversible upon viral clearance [ 11 ]. Increased levels of TGF- β and IL-15 were found in patients who spontaneously cleared HCV infection, while those patients with persistent infection presented elevated levels of CCL-5 and IL-8 [ 30 ]. Considering chemokine set, a decrease in CCL-2, CCL-4, and CXCL-10 levels were reported in HCV genotype 2- and 3-infected patients after antiviral treatment, with lower levels of CCL-4 at baseline associated to an early response to treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%